HLA‐Cw6 allele and efficacy of secukinumab. (2nd November 2018) - Costanzo, A.; Bianchi, L.; Flori, M.L.; Malara, G.; Stingeni, L.; Bartezaghi, M.; Carraro, L.; Castellino, G.; ,
Summary: This study from Italy looked at the response of adults with moderate‐to‐severe psoriasis to secukinumab, a form of treatment known as a human monoclonal antibody, and in particular whether people with a specific gene called HLA‐Cw6 did better or worse. Individuals with this gene are 10 times more likely to develop psoriasis, and their psoriasis is more likely to start early in life and be more severe. Another human monoclonal antibody, ustekinumab, has been shown to produce a quicker and better response in people with the HLA‐Cw6 gene than without. The particular type of psoriasis under investigation in this study was the one where people have long‐lasting large, red, raised, flat areas of psoriasis with a silvery scale (chronic plaque psoriasis). The study confirmed a couple of things that were known already: for instance, that secukinumab is a very effective treatment that works quickly. Also, as one would expect, the group of patients with the HLA‐Cw6 gene were, on average, younger than the group without, and their psoriasis had started at a younger age. With regard to the HLA‐Cw6 gene itself, it was tested for in 431 of the 434 patients originally enrolled into the study. Thirty‐two patients dropped out. Of the remainder, the 227 patients with the HLA‐Cw6 gene did no better after 24 weeks' secukinumab treatment than the 172 without it. In other words, secukinumab appeared to be equally effective in both groups, and there seems to be no reason to test for the gene before starting treatment. Abstract : Linked Article:  Costanzo et al. Br J Dermatol 2018; 179 :1072–1080